Features of the Conjugation of Higher Education and the Labor Sphere in the Context of Structural Transformations of the Domestic Higher Education System - V. S. Senashenko; E. P. Struchkova (Высшее образование в России, 2025)
The subject of this work is the study of the problem of conjugation of higher education and the labor sphere using various algorithms of normative and methodological description of the structure of qualification of a graduate of higher education (hereinafter referred to as academic qualification) and the qualification of a working specialist (hereinafter referred to as professional qualification). It is shown that the imperative of readiness of a graduate of higher education immediately after receiving a diploma of higher education to comply with the labor market, that is, the requirements of the employer, as well as the goals of the company or enterprise with the existing organization of the educational process is largely an ephemeral construction. A new algorithm is proposed and the degree of expediency of using the concept of “competence” in the interface of the system of higher education and the labor sphere is revealed. It is confirmed that its use in the educational context with the existing organization of the educational process creates additional difficulties in solving the problem under consideration.